In vivo Reflectance Confocal Microscopy: A Useful Tool to Select the Location of a Punch Biopsy in a Large, Clinically Indistinctive Lesion - Malou Peppelman; Esther A.W. Wolberink; Roland J.J. Koopman; Piet E.J. van Erp; Marie-Jeanne P. Gerritsen (Karger Publishers, 2013)
Reflectance confocal microscopy (RCM) is a noninvasive technique for in vivo imaging of the skin that allows evaluation of the total lesion area. This case report about a 66-year-old patient with a clinically indistinctive, previously treated erythematous lesion on the frontal part of the face demonstrates the use of RCM to select the proper biopsy location.